Effect of Corneal Incision Enlargement on Surgically Induced Astigmatism in Biaxial Microincision Cataract Surgery - Tetikoğlu, Mehmet (Turk J Ophthalmol, 2016)
OBJECTIVES: To evaluate surgically induced astigmatism (SIA) in biaxial microincision cataract surgery with enlargement of one corneal incision during intraocular lens implantation (IOL). MATERIALS AND METHODS: Data from 683 eyes with cataract that underwent biaxial microincision cataract surgery and IOL were retrospectively analyzed. The operated eyes were divided into 4 groups defined by final corneal incision length after IOL implantation. There were 83 eyes with 1.6 mm corneal incisions (group 1) and 200 eyes in each of the 2, 2.4, and 2.8 mm corneal incision groups (groups 2, 3 and 4, respectively). SIA was assessed using preoperative and postoperative keratometric values at one month. RESULTS: The mean magnitude of SIA was 0.83±0.4 D in group 1, 0.93±0.5 D in group 2, 1.03±0.6 D in group 3 and 1.04±0.7 D in group 4. The SIA showed statistically significant differences between the four groups (p=0.05). Pairwise group comparisons revealed significant differences between groups 1 and 3 and groups 1 and 4 (p=0.005). CONCLUSION: Biaxial microincision cataract surgery with an incision size of 1.6 mm resulted in the least SIA. Enlargement of the corneal incision beyond 2.0 mm during IOL implantation led to significant increases in SIA. We believe that with the development and dissemination of IOLs which can be inserted through small corneal incisions, biaxial microincision cataract surgery will be the best choice to prevent SIA and increase visual acuity.